TIPS OF NURSING (CARING) TO IMPROVE QUALITY OF NURSING CARE - Prawesti, Dian (Jurnal Penelitian STIKES Kediri, 2012)
Nursing is a form of professional service that is based on nursing tips. Nursing tips are an interpersonal relationship process and an interaction between nurse and patient in social environment during nursing care given. One of Nursing tips is nurse’s caring, when if it is done properly and according to the standards, it can improve the quality of nursing services. The study was conducted to analyze the relation between nurse’s caring tips and quality of treatment service at inpatient Installation Kediri Baptist Hospital. The design was cross sectional design. The population included patients in Class 2 and Class 3A at inpatient Installation Kediri Baptist Hospital. The total sample of 96 respondents taken based on the inclusion criteria. The independent variable was nurse’s caring tips. The dependent variable was quality of treatment service. Data were collected using structural questionnaire. Then data were analyzed using Spearman’s Rho test with significance level of 0,05. The results obtained tips of nurses caring related to quality of care with p = 0,000 and r = 0,675 and constituted positive correlation.It was concluded that the tips of good caring nurses can improve the quality of nursing care at Baptist Hospital Kediri.